Analisis ketahanan pangan keluarga dan pendapatan sebagai determinan status gizi balita di Kabupaten Ende - Dadi, Maria Eugenia Hestina; Sumardiyono, Sumardiyono; Anantanyu, Sapja (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Nutritional problems in children under five, especially malnutrition, are still a challenge in Indonesia, including in East Nusa Tenggara Province. Based on the latest data, the prevalence of underweight toddlers reaches 22%, obesity 2%, and stunting 15,5%. Family food security and income levels are important factors that affect the fulfillment of children's nutritional intake, which ultimately impacts nutritional status.Objectives: This study aims to analyze the relationship between family food security and income level to the nutritional status of toddlers aged 24–59 months in Ende Regency.Methods: This study used an analytical observational design with a cross-sectional approach. The sample consisted of 194 mothers and toddlers aged 24–59 months who were selected in Ende District and Central Ende District, which was carried out from December 2024 to February 2025. Independent variables include family food security and income level, while dependent variables are the nutritional status of toddlers. Data analysis was carried out using the Chi-Square test.Results: The study showed that there was a significant relationship between family food security and the nutritional status of toddlers (p = 0,000), as well as is not between income level and nutritional status of toddlers (p = 0,646) in Ende and Central Ende Districts.Conclusion: Family food security and income level were significantly related to the nutritional status of toddlers aged 24–59 months in Ende Regency.